ISU DIKOTOMI PENDIDIKAN SEKOLAH DAN LUAR SEKOLAH - Sukari; Farid Al Fani; Agus Sutrisno (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
The dichotomy between school education and out-of-school education remains a fundamental issue in the Indonesian education system. School education is often perceived as the primary and most legitimate educational pathway, while out-of-school education is positioned merely as a complementary alternative. This dichotomous perspective has implications for policy inequality, public perception, and recognition of learning outcomes. This study aims to analyze the nature of the dichotomy between school and out-of-school education, examine its historical and sociological roots, and identify integrative solutions within the national education system. This study employs a qualitative approach using a literature review method. The findings indicate that the educational dichotomy is a socio-historical construction influenced by colonial legacy, educational policy orientation, and societal perceptions of formal credentials. Therefore, an integrative approach emphasizing lifelong learning, cross-sector collaboration, and recognition of non-formal and informal learning is essential.